DEVELOPMENT OF HEURISTIC SCHEDULING METHODE FOR FINAL ASSEMBLY AREA BASED ON SPLITTING AND CRASHING APPROACHES - Rozy Abdul Azis, Fahrul
The air craft final assembly process is different from the general product assembly process. In the product assembly process in general, components will move through several work stations on the assembly line. However, at the final assembly of the aircraft, the sub-assembly components will be collected to one place to be assembled. That is because the size and weight of aircraft components will make it difficult to move the product if the process is from one work station to another work station. The final assembly process for the aircraft type Y is divided into 316 activities. At the final assembly there are several work projects that have their own characteristics. In the implementation of projects, there are often obstacles such as the delay in the completion of the project which can cause problems, such as the swelling of project expenditures far beyond the budgeted funds, there are complaints and loss of trust from customers, and to the failure or inability of the project implementing company to complete the project. Such failure can certainly threaten the safety of the project implementing company and will create a huge loss, but these failures can be overcome earlier. To overcome these problems, a structured and well-integrated management is needed. This study aims to be able to meet the desired target cycle time with minimal costs. Characteristics of activities in research that cover a lot of activities so that work optimization is done by using the splitting and crashing approches to be able to complete the final assembly activity.